A configuration perspective of absorptive capacity in environmental management practice - Soetanto, Danny; Huang, Shuangfa; Mahmud, Muaz; Jack, Sarah (Taylor and Francis Group, 2022)
Environmental management is becoming a popular practice in many organisations. However, the transition from old to new practices does not come without any challenges. Numerous studies have argued that the process of adopting a new practice such as environmental management will depend on firms’ absorptive capacity, i.e. the ability of firms to identify, acquire and transform external information and knowledge. However, absorptive capacity alone does not guarantee success. To deliver the intended outcomes, absorptive capacity works in conjunction with other internal and external factors. Based on a configuration perspective, this study used data from 107 manufacturing firms to identify an asymmetric role played by absorptive capacity with factors, such as firm size, decentralisation, customer engagement and global environmental awareness in supporting the practice of environmental management. This study contributes to the development of knowledge in environmental management literature and provides several practical recommendations.